Finiteness of analytic cohomology of Lubin-Tate (φL,ΓL)-modules - Steingart, Rustam (Journal of number theory, 2024)
We prove finiteness and base change properties for analytic cohomology of families of L-analytic (φL,ΓL)-modules parametrised by affinoid algebras in the sense of Tate. For technical reasons we work over a field K containing a period of the Lubin-Tate group, which allows us to describe analytic cohomology in terms of an explicit generalised Herr complex.
Online verfügbar: 17. Mai 2024, Artikelversion: 24. Mai 2024
Gesehen am 18.11.2024